Use of Fairy Tales as a Communication Media in Character Formation in Aisyiyah Bustanul Athfal Kindergarten - Siregar, Widy Farah Muthiah; Andini, Riska Tri; Munthe, Rizkini Yana; Anggraini, Elya Siska (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research activity was held to find out the impact of using audio-visual learning media in the form of fairy tales on character formation in Aisyiyah Bustanul Athfal Kindergarten. The location of the kindergarten is on Jl. A.R Hakim, Ex. Nangka, North Binjai, North Sumatra. This research uses qualitative research methods to obtain clear and accurate research results. From the conclusions of the research results at Aisyiyah Bustanul Athfal Kindergarten, fairy tales are very good to use as a communication medium in forming the character of early childhood.